2017
DOI: 10.1111/bcp.13207
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual and interethnic variability in drug disposition: polymorphisms in organic anion transporting polypeptide 1B1 (OATP1B1; SLCO1B1)

Abstract: OATP1B1 (SLCO1B1) is predominantly expressed at the basolateral membrane of hepatocytes and is critically important for the hepatic uptake and clearance of numerous drug substrates and endogenous compounds. In general, the organic anion transporting polypeptides (OATP; SLCO) represent a superfamily of uptake transporters that mediate the sodium-independent transport of a diverse range of amphipathic organic compounds including bile salts, steroid conjugates, thyroid hormones, anionic peptides, numerous drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 68 publications
(101 reference statements)
4
77
0
1
Order By: Relevance
“…Human OATP1B plays pivotal roles in the hepatic uptake of a diverse array of anionic drugs. [7][8][9] As expected, potent OATP1B inhibitors, such as cyclosporine A and rifampicin, have been shown to increase (2-fold to 16-fold) the area under the plasma concentration-time curve (AUC) of OATP1B substrate drugs (UW Drug Interaction Database Program, https ://www.drugi ntera ction info.org/). We and other groups have demonstrated significant increases in the plasma concentrations of endogenous substrates such as bilirubins, coproporphyrins, amidated and nonamidated bile acids (including glucuronide and sulfate conjugates), and dicarboxylates following a single dose of cyclosporine A, rifampicin, and selected NCEs with OATP1B inhibition potential.…”
Section: Articlementioning
confidence: 73%
See 1 more Smart Citation
“…Human OATP1B plays pivotal roles in the hepatic uptake of a diverse array of anionic drugs. [7][8][9] As expected, potent OATP1B inhibitors, such as cyclosporine A and rifampicin, have been shown to increase (2-fold to 16-fold) the area under the plasma concentration-time curve (AUC) of OATP1B substrate drugs (UW Drug Interaction Database Program, https ://www.drugi ntera ction info.org/). We and other groups have demonstrated significant increases in the plasma concentrations of endogenous substrates such as bilirubins, coproporphyrins, amidated and nonamidated bile acids (including glucuronide and sulfate conjugates), and dicarboxylates following a single dose of cyclosporine A, rifampicin, and selected NCEs with OATP1B inhibition potential.…”
Section: Articlementioning
confidence: 73%
“…Human OATP1B plays pivotal roles in the hepatic uptake of a diverse array of anionic drugs . As expected, potent OATP1B inhibitors, such as cyclosporine A and rifampicin, have been shown to increase (2‐fold to 16‐fold) the area under the plasma concentration‐time curve (AUC) of OATP1B substrate drugs (UW Drug Interaction Database Program, https://www.druginteractioninfo.org/).…”
mentioning
confidence: 77%
“…First, the NHIS database contains information on a population that is ethnically homogeneous. Studies suggested an interethnic variability in pharmacologic responses to medications . For example, Asian individuals are more responsive to the beneficial effects of statins .…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested an interethnic variability in pharmacologic responses to medications. [39][40][41][42][43] For example, Asian individuals are more responsive to the beneficial effects of statins. 39 Also, differences in responses to antihypertensive medications exist between whites and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…To date, almost 200 SNPs in the SLCO1B1 gene have been described, some of them very frequent, such as c.388A>G (p.Asn130Asp, rs2306283), whose minor allele frequency (MAF) is 42.8%. This variant has less capacity to transport certain drugs, for instance, repaglinide [9,10]. However, this does not result in an important impact on the pharmacokinetics, response and toxicity of these drugs.…”
Section: Organic Anion-transporting Polypeptides (Oatps)mentioning
confidence: 99%